Interim results from the CATNON trial (EORTC study 26053-22054) of treatment with concurrent and adjuvant temozolomide for 1p/19q non-co-deleted anaplastic glioma: a phase 3, randomised, open-label intergroup study - Van den Bent, Martin J.; Wick, Wolfgang (The lancet, 2017)
Summary Background The role of temozolomide chemotherapy in newly diagnosed 1p/19q non-co-deleted anaplastic gliomas, which are associated with lower sensitivity to chemotherapy and worse prognosis than 1p/19q co-deleted tumours, is unclear. We assessed the use of radiotherapy with concurrent and adjuvant temozolomide in adults with non-co-deleted anaplastic gliomas. Methods This was a phase 3, randomised, open-label study with a 2 × 2 factorial design. Eligible patients were aged 18 years or older and had newly diagnosed non-co-deleted anaplastic glioma with WHO performance status scores of 0-2. The randomisation schedule was generated with the electronic EORTC web-based ORTA system. Patients were assigned in equal numbers (1:1:1:1), using the minimisation technique, to receive radiotherapy (59·4 Gy in 33 fractions of 1·8 Gy) alone or with adjuvant temozolomide (12 4-week cycles of 150-200 mg/m2 temozolomide given on days 1-5); or to receive radiotherapy with concurrent temozolomide 75 mg/m2 per day, with or without adjuvant temozolomide. The primary endpoint was overall survival adjusted for performance status score, age, 1p loss of heterozygosity, presence of oligodendroglial elements, and MGMT promoter methylation status, analysed by intention to treat. We did a planned interim analysis after 219 (41%) deaths had occurred to test the null hypothesis of no efficacy (threshold for rejection p<0·0084). This trial is registered with ClinicalTrials.gov, number NCT00626990. Findings At the time of the interim analysis, 745 (99%) of the planned 748 patients had been enrolled. The hazard ratio for overall survival with use of adjuvant temozolomide was 0·65 (99·145% CI 0·45-0·93). Overall survival at 5 years was 55·9% (95% CI 47·2-63·8) with and 44·1% (36·3-51·6) without adjuvant temozolomide. Grade 3-4 adverse events were seen in 8-12% of 549 patients assigned temozolomide, and were mainly haematological and reversible. Interpretation Adjuvant temozolomide chemotherapy was associated with a significant survival benefit in patients with newly diagnosed non-co-deleted anaplastic glioma. Further analysis of the role of concurrent temozolomide treatment and molecular factors is needed. Funding Schering Plough and MSD.